SPIRITUAL AND MORAL IDEAS IN THE WORKS OF ALISHER NAVOI AND THEIR EXPRESSION IN LINGUISTIC UNITS - Uzaqova Lola Abdurashitovna (Modern American Journals, 2025)
This article examines the spiritual and moral concepts embodied in the works of Alisher Navoi and the ways in which they are expressed through linguistic units. It analyzes how key ethical categories such as perfection, justice, generosity, purity, and humanism are reflected through lexical, phraseological, and stylistic means. The study also explores Navoi’s use of artistic imagery, symbolism, metaphors, and Sufi terminology, clarifying their semantic functions within the texts. The research highlights the importance of Navoi’s works in moral education and their relevance in shaping the spiritual worldview of contemporary youth.
Keywords: Alisher Navoi, spiritual and moral ideas, linguistic units, Sufism, symbolism, metaphor, stylistic devices, ethics, perfection.